PERAN PEMERINTAH DESA DALAM PELAKSANAAN PROGRAM TANAM BAWANG MERAH DI DESA SUNGAI GERINGING KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR TAHUN 2014 - Madani, Apri; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this study was to determine the role of Village government in implementing the program of planting onions in Village Sungai Geringging and to determine the factors inhibiting and supporting the role of Village government in the implementation of the program of planting onions in Village Sungai Geringging.This research was conducted in the of Village Sungai Geringin Kecamatan Kampar Kiri, Kabupaten Kampar district in Riau province. In determining informant in this study determined people who know and get involved in the program of planting onions in Village Sungai Geringin Kecamatan Kampar Kiri, Kabupaten Kampar, then the necessary data, including primary data and secondary data. For data collection techniques done by interview, observation and literature study. Data analysis method used in this research is qualitative descriptive analysis method.The village governments role in the implementation of the program of planting onions in Village Sungai Geringging include: 1) improving the quality of human resources of farmers through extension activities and training for farmers onion. 2) provide capital assistance through a revolving fund for farmers onion, this event seeks to help the onion farmers in order to increase agricultural output onion. Assistance provided in the form of compost, seedlings of onion and some farm implements. 3) improve the marketing network of onion because farmers prefer to sell their harvest in place / in the fields. 4) the provision of infrastructure /agricultural infrastructure onion. The inhibiting factor onion planting program in Village Sungai Geringging are 1) lack of human resources involved in implementing the program of planting onions in Village Sungai Geringging, both in terms of village government and farmers groups onion. 2) the limited budget given to the farmer groups onion in Village Sungai Geringging. 3) the environmental conditions in Village Sungai Geringging erratic which has an impact on the growth of onion in Village Sungai Geringging.Keywords: Role, the Village Government, Planting Program Shallots